Analisa Mengenai Garam dan Terang Dunia bagi Saksi Kristus Berdasarkan Kitab Matius 5 : 13 -16 - Edward Edward; Christofer Cahyadi; Djuwansah Suhendro P Stephanus; Eunike Eunike; Evi Sondang Pangaribuan (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
In Christian tradition, the call to be the salt and light of the world is a well-known teaching, yet its profound meaning is often overlooked. This study aims to explore the significance and application of Jesus' teaching in Matthew 5:13-16, where He commands His followers to function as salt that enhances flavor and light that dispels darkness in the world. The research methodology used is a hermeneutical textual analysis, focusing on the historical and social context in which this text was delivered. This study discusses the distinct functions of salt and light and their relevance in the everyday life of Christians. The findings highlight that salt and light are not merely roles but are essential identities of a Christian that should be reflected in their lives. A key insight from this study is the understanding that while salt works invisibly, it has a significant impact, while light must be visible to drive out darkness. The research confirms the importance of Christians as agents of change through lives that reflect Christ's love and truth. In conclusion, being the salt and light of the world requires sacrifice and the willingness to live according to Christ's teachings, bringing positive impact to one's surroundings and glorifying God.